2001
DOI: 10.1111/j.1471-0528.2001.00298.x
|View full text |Cite
|
Sign up to set email alerts
|

Factor V Leiden and G20210A prothrombin mutations are risk factors for very early recurrent miscarriage

Abstract: Objective To determine whether there is an association between early recurrent miscarriage (before 10 weeks of pregnancy) and Factor V Leiden and G20210A prothrombin mutations. Design A prospective study.Setting Department of Gynaecology and Obstetrics, Saint Antoine Hospital, Paris, France.Population Two groups of women: those with early unexplained recurrent miscarriage before 10 weeks of pregnancy (n ¼ 260) and control healthy women without a previous history of thromboembolism (n ¼ 240). Methods Screening … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
1
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 25 publications
1
47
1
2
Order By: Relevance
“…Indeed, a difference in FVL carriage between both groups was also reported in several studies [20,36,37]. The investigation of Roque et al [20] reported a reverse association between FVL carriage and embryonic losses (OR 0.23; 95% CI 0.07-0.77) and no association with RPL at postembryonic stage (OR 1.07; 95% CI 0.46-2.5).…”
Section: Factor V Leiden Carriage In Patients With Miscarriagementioning
confidence: 68%
“…Indeed, a difference in FVL carriage between both groups was also reported in several studies [20,36,37]. The investigation of Roque et al [20] reported a reverse association between FVL carriage and embryonic losses (OR 0.23; 95% CI 0.07-0.77) and no association with RPL at postembryonic stage (OR 1.07; 95% CI 0.46-2.5).…”
Section: Factor V Leiden Carriage In Patients With Miscarriagementioning
confidence: 68%
“…Few case-control studies and meta-analysis had shown a high prevalence of FVL in women with RPL [3, 10, 2831]. A systematic review of the literature found an OR for the association between RPL and FVL of 2.0 (95% CI 1.5–2.7; P < .001) [3].…”
Section: Discussionmentioning
confidence: 99%
“…8 In fact, it has been postulated that maternal thrombophilia could be a risk factor for fetal loss because of the production of microthrombosis on placental bed vessels and placental infarctions, which produce a compromise in the fetomaternal circulatory system, that results in low placental perfusion and eventually in fetal loss. 9,10 …”
Section: Discussionmentioning
confidence: 99%